Investment Climate Factors in the Baltic Countries - Misiūnas, Algimantas; Gudeliauskaitė, Dovilė (Lithuanian Journal of Statistics, 2013)
This paper examines the investment climate factors in Lithuania, Latvia and Estonia. It discusses the factors within the firm and country level; highlights relevant key factors common to all countries that affect the investment climate and increase the country’s attractiveness to foreign investors; discusses the main macroeconomic indicators, the most important foreign investors, shows real situation and considers the factors and areas that require government’s attention on investing in improving the situation; provides comparable national data allowing comparison between the countries, as well as to the overall investment climate in the Baltic countries; presents the theoretical and practical investment climate factors in the final conclusions and suggestions.
Keywords: Baltic countries; investment climate factors; investment environment